MODERNIZING OF JAVANESE WOMEN DRESSING STYLE CULTURE IN 20TH CENTURY: THE EDUCATION IMPACT - Moch. Dimas Galuh Mahardika (Haluan Sastra Budaya, 2022)
The Dutch colonialism not only leaves stories about exploitation, the breakdown of social strata, and other inhumane stories. On the other hand, the presence of Dutch colonialism in Nusantara gives the influence of modern culture to several aspects of bumiputra people's lives. After the colonization runs for centuries in Nusantara, the colonial government seems to have the awareness for"return the favor" to the bumiputra people by implement the Ethical Policy that are aimed at improving the welfare of bumiputra people. After the enactment of Ethical Policy, Javanesse people get into the modernization, one of them in the education aspect. After receiving the western education models, Javanese women began more often wearing the western dressing style. This article try to explain the women history in the appearance style aspects as the one of implementation education impacts by the colonial government for the bumiputra people.